Plan estratégico de marketing para la empresa de yogurt orgànico don alipio, cantón Quevedo, periodo 2014-2017 - Montiel Bueno, Armando Amado (2015)
The food industry in Ecuador is one of the most important, because foods are consumer products and the customer always wants variety, quality and fair prices. This sector offers consumers unlimited food but not all have adequate nutritional situation for consumers; for example, some products contain dyes and preservatives too causing health problems. For this you must make important decisions about nutrition that affect the improvement of the health of the entire population, especially children and the elderly. For these reasons is to create a production microenterprise and marketer of organic fruit yogurt Don Alipio, which offer consumers a product made with raw materials of excellent quality, with different flavors to the market offers such as strawberry, fig and strawberry, under the most appropriate to avoid any contamination and ensure the final consumer a product of excellent quality pro productive process. The competitive advantage that will differentiate Don Alipio Organic Yogurt is the product quality and price, because as mentioned previously the best raw materials for the manufacture of the product is used, without this meaning too high a price increase .The product price is very competitive compared with other….